2013
DOI: 10.1002/app.40155
|View full text |Cite
|
Sign up to set email alerts
|

Imparting antimicrobial properties to natural rubber latex foam via green synthesized silver nanoparticles

Abstract: The green synthesis of silver nanoparticles (AgNPs) in centrifuged natural rubber latex (NRL) by in situ reduction of silver nitrate by NRL is described. The synthesis of AgNP within NRL was successfully carried out without the addition of any reducing agent or stabilizers. The modified AgNP incorporated with centrifuged NRL (GAgNP_NRL) was used to make NRL foam (NRLF) by the Dunlop production method. An ultraviolet-visible (UV-Vis) spectrophotometer analysis, Zeta potential analysis data and transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 52 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…Initially, the mixture (1% latex + AgNO 3 ) appeared white (Figure 1A); however, following the incubation period, a light greyish color was observed (Figure 1B). Rathnayake et al [28], reported a similar color change for the green synthesis of AgNPs inside centrifuged natural rubber latex. These visible color changes are usually related to the reduction in silver (Ag) ions by the capping of biomolecules present within the respective extracts [5,28].…”
Section: Visual Inspection Uv-visible Spectroscopy and Quantification...mentioning
confidence: 78%
See 1 more Smart Citation
“…Initially, the mixture (1% latex + AgNO 3 ) appeared white (Figure 1A); however, following the incubation period, a light greyish color was observed (Figure 1B). Rathnayake et al [28], reported a similar color change for the green synthesis of AgNPs inside centrifuged natural rubber latex. These visible color changes are usually related to the reduction in silver (Ag) ions by the capping of biomolecules present within the respective extracts [5,28].…”
Section: Visual Inspection Uv-visible Spectroscopy and Quantification...mentioning
confidence: 78%
“…Rathnayake et al [28], reported a similar color change for the green synthesis of AgNPs inside centrifuged natural rubber latex. These visible color changes are usually related to the reduction in silver (Ag) ions by the capping of biomolecules present within the respective extracts [5,28]. Moreover, the literature has often associated a rapid and extreme color change with the production of AgNPs; however, this may vary based on several factors such as plant organ type, solvent/extract, concentration, duration of incubation, and the presence of reducing agents [29,30].…”
Section: Visual Inspection Uv-visible Spectroscopy and Quantification...mentioning
confidence: 78%
“…Qualitative determination of antimicrobial properties was performed as described in the following method as reported in the literature. [18,[22][23][24] Luria broth (LB) medium was prepared and a single colony of Escherichia coli (E. coli) was inoculated in aseptic conditions. Bacteria inoculated LB medium was then incubated at 37 C for 12 h in a mechanical shaker.…”
Section: Antibacterial Propertiesmentioning
confidence: 99%
“…The focus is on exploring the mechanical properties of composite foams and emphasizing the reuse of natural fibers. Currently, the research on antibacterial NRLF mainly focuses on zinc oxide [34] and silver particles [35][36][37][38][39]. Khemara Mama [40] demonstrated that NRLF treated with silver nanoparticles of only 0.2 per hundred rubber (phr) had improved antibacterial ability by 43.8% against E. coli and 25% against S. aureus compared to NRLF that was not treated with silver nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with zinc oxide and silver particles, chitin has the advantages of renewability, biodegradability and biocompatibility. Furthermore, the preparation of silver antimicrobials is quite complex due to the synthesis of nanoparticles [39] while blending with chitin is more simple and convenient. The poor solubility of chitin provides the NRLF composite with more durability within its service life.…”
Section: Introductionmentioning
confidence: 99%